As brincadeiras e os brinquedos de crianças, tem gênero? representações sociais das professoras da Creche Escola Elza Maria Rodrigues da Silva - PINHEIRO, Delza Cristina (2023)
This research is part of a professional master's degree, in the Graduate Program in Basic Education Teaching Management, at the Federal University of Maranhão UFMA. It is developed from the following problematizing question: How do the social representations of gender of teachers influence the choices of games and toys of children in early childhood education at the Maria Elza Rodrigues da Silva daycare center? The general objective of this study is to investigate how the teachers' social representations of gender influence the choices of games and toys of the children of the early childhood education of the Maria Elza Rodrigues da Silva Nursery, aiming at the collective construction of a Play Notebook. The specific objectives are aimed at understanding how free play takes place in the school environment without gender distinctions, allowing children to cross the boundaries of play; describe and analyze how girls and boys participate in play and what roles they play, using imagination and playfulness to compose their identity; analyze the knowledge that teachers demonstrate about gender issues in early childhood; build an educational product (Caderno do Brincar) to overcome gender inequalities among children in early childhood in the collective spaces of educational institutions, in order to minimize the impacts caused by manifestations of prejudice, sexist ideas and gender differentiations. The methodology for the development of the research is qualitative in nature, framed as a case study, adopted as data collection techniques the non participant observation and semi-structured interviews as a research instrument. The research presents as an educational product the Caderno do Brincar, which consists of a guide of didactic-pedagogical guidelines, which will serve as an instrument to guide teachers in their practices, in the perspective of building an Education for Gender Equality. With the production of knowledge resulting from this research, we hope to contribute so that children's education spaces are places where girls and boys receive not only care, but also have possibilities of socialization, from a plural education so that they are protagonists in the fight against prejudice, discrimination to overcome inequalities between women and men.